Identify Of Floc-Forming Bacteria In Shrimp Pond In Pangkep District - Sukmawati Sukmawati (UNIVERSITAS NEGERI PADANG, 2017)
This research aims to identify the kinds of floc-forming bacteria in shrimp pond in Pangkep District. This study was a descriptive research. Floc-forming bacteria were isolated from the water and mud samples. According to microbial technique isolation procedure, by using Nutrient Agar (NA) as isolation medium. The result of this study showed that there were 37 isolates. And Then floculated activity was measured: The result showed the theme 5 isolates which have more than 79% of floculating activity namely, isolat 1,isolat 2, isolat 3, isolat 4, isolat 5, floculating activity: 90,34%, 90,34 %, 94,03%, 79,68%, 92,47% respectively. At can be cocluded that isolat 1. Enterococcus sp, isolat 2. Bacillus spdan isolat 3. Vagococcus sp..Keywords: Identification, floc-formingbacteria,shrimp pond